Realization of economic competition in the field of public procurement - Zelmat, Sofiane (Journal of Human Sciences, 2023)
The important role That the principle of free competition plays in the economic field by increasing the effectiveness of economic dealers by leaving freedom of competition between them in the context of freedom of trade and industry, Also that considering Public procurements as one of the important topics in the economic field Because it attached to public money and being among the most important fields of competition for these economic dealers, The Algerian legislator had to implement the principle of free competition in the field of Public procurements, Hence, obliging the economic operator to respect the principle of freedom of competition and observed it during all stages of the conclusion of the Public.